Calibration of VISSIM for an urban corridor under heterogeneous traffic conditions - Muhammad Azam, .; Sitti Asmah, Hassan; Othman, Che Puan (Giordano Editore, 2024)
The replication of heterogeneous traffic conditions in simulation tools is a challenging task due to involvement of various vehicle classes and their associated driving behaviours. Despite considerable efforts have been made in literature, further attention is still needed due to the complexity of heterogeneous traffic mixes, particularly for urban corridors with closely spaced intersections. In the present study, a systematic calibration procedure for VISSIM has been proposed by considering the vehicle-class specific driver behaviour parameters. The proposed procedure involved four key steps including; identification of sensitive parameters via sensitivity analysis, generation of random samples by using Latin Hypercube Design (LHD), development of regression model based on LHD samples and VISSIM output, and the use of regression model in Microsoft Excel Solver program to determine candidate parameter set producing measure of effectiveness (MOE) values closer to field values. After calibration, the model validation was also conducted which was done by assessing the statistical similarity between field and simulation data sets via paired t-test. The study concluded that the vehicles in heterogeneous traffic conditions tend to adopt smaller longitudinal and lateral gaps during standing and driving conditions. The proposed methodology can help the practitioners in developing simulation models for similar traffic conditions.